THU0254 In Vivo Ubiquinol (COQ10) Supplementation Reduces The Atherothrombotic Status of Antiphospholipid Syndrome Patients. (15th July 2016) - Perez-Sanchez, C.; Aguirre, M.Ά.; Arias-de la Rosa, I.; Ruiz-Limόn, P.; Barbarroja, N.; Άbalos, M.C.; Jiménez-Gόmez, Y.; Segui, P.; Collantes-Estévez, E.; Villalba, J.M.; Fernández-del Rio, L.; Gonzalez-Reyes, J.A.; et al.
Abstract : Background: Previous studies have demonstrated the presence of an oxidative perturbation in antiphospholipid syndrome (APS) patient's leukocytes, which was directly related to an inflammatory and proatherothrombotic status, and relied on alterations in mitocondrial dynamics and metabolism, which was prevented and/or reversed by in vitro treatment with coenzyme Q10 (CoQ10). Objectives: 1) To investigate the beneficial effects of in vivo ubiquinol (Q, reduced form of CoQ10) supplementation on atherothrombosis prevention in APS patients, through the implementation of a prospective, randomized, double-masked, placebo-controlled study. 2) To characterize the cellular and molecular mechanism involved. Methods: The study was conducted on 32 APS patients randomized to receive either Q (200 mg/day) or placebo for one month. Blood was drawn at time 0 and at the end of the treatment. Studies were performed in plasma and purified leukocyte subsets. Endothelial activity was evaluated by Laser-Doppler measurement of post ischemic reactive hyperemia. Carotid intimae media thickness (CIMT) was measured as atherosclerosis marker. Results: Twenty nine out of the 32 APS patients completed the intervention, which increased significantly plasma Q levels. Endothelial function improved notably. Q treatment decreased expression of a number of protrombotic and proinflammatory mediators, and produced a reduction in both, the levels of peroxides and the percentage of monocytes with altered mitochondrial membrane potential (ΔΨm). Electron Microscopy analyses indicated that Q treatment promoted an increase in monocytes' mitochondrial size. MiRNA profiling by Nanostring technology revealed 22 microRNAs reduced in APS patients. Among them, 10 were upregulated by effect of Q treatment. Functional classification of those miRNAs revealed a preponderance of target mRNAs involved in cardiovascular disease. Gene profiling showed differential expression of 33 atherosclerosis-related genes in APS patients, of which 16 were changed by effect of Q. Using bioinformatic tools, interaction networks of those genes and microRNAs were also identified (i.e. downregulation of PDGFB, IL-1A and SERPINE1 was associated to upregulation of miR150–5p; in parallel, downregulation of TGFB2 and MMP-1 was linked to the upregulation of miR-145–5p). Correlation studies demonstrated that reduced expression prothrombotic and proinflammatory mediators, and increased miRNA expression, were related to the increased plasma Q levels and improved endothelial function. Q effects were particularly relevant in APS patients showing pathologic CIMT and thrombotic recurrences, who showed a better response to Q treatment. Conclusions: 1) Q supplementation significantly improved endothelial function, and reduced mitochondrial dysfunction, oxidative stress and the expression of prothrombotic/proinflammatory proteins. 2) Underlying epigenetic mechanisms seem to be involved. Our results support the potential impact of Ubiquinol in the prevention of atherothrombosis in APS patients. Acknowledgement: Supported by CTS-7940, PI12/01511, PI15/01333, KANEKA. Disclosure of Interest: None declared